The Influence Of Temperature and Contact Time On Waste Cooking Oil’s Adsorption Using Bagasse Adsorbent - Sera, Rantiana; Lesmana, Donny; Maharani, Atika (Inovasi Pembangunan : Jurnal Kelitbangan, 2019)
Cooking oil is one of basic needs that very often used by public. Cooking oil that has been used it will occur characteristic’s change and if consderated from chemical composition it has carcinogen content. One way of doing things for used cooking oil is adsorption method. Goal of this research for reduce Free Fatty Acid content and color changes on used cooking oil used bagasse adsorbent, with variant adsorption temperature 32, 40, and 50oC, also contact time as 45, 90, and 180 minutes. Best results of this research are FFA 85.10% reduction occur at 40-50oC with 180 minutes contact time and the biggest color change occur at 50oC with 180 contact time is 14.925%.